The pattern of contact lens uses among university female students at Hafr Al-Batin university, Saudi Arabia - G. Mohamed, Asmaa; M. Gomaa, Salma (International Journal of Advanced Nursing Studies, 2019)
Background: Contact lens (CL) are widely used in Saudi Arabia, and interest in the lens among the population is increasing rapidly especially among the younger population. CL has become more important as an optical correction method. Many people compromise their visual health due to bad habits for wearing a contact lens.Aim: The present study aimed to assess the pattern of CL uses among university female students.Methods: Descriptive cross-sectional study design was used. 225 students were agreed to participate in the study from four colleges. A structured questionnaire was developed to collect necessary information regarding; socio-demographic characteristics, history of using CL and eye complains.Results: The findings revealed that the majority 74.7% of university students using lens mostly for cosmetic purpose and 45.2% wear CL from 5-12/day.Conclusions: Based on the results of the present study, health education programs incorrect and careful practice regarding CL wear should be directed to the university students to prevent complications resulting from the wearer's inappropriate behavior.Â Â Â